Code Switching in Line Group Chatting Used by Students of English Department in Udayana University - Cahyaning Putri, Adisthina (Humanis, 2018)
Code switching is a phenomenon which can be found in our daily conversations even both in written or spoken. Code switching refers to the use of two languages within a sentence or discourse. This study entitled Code Switching in Line Group Chatting used by English Students of English Department in Udayana University used qualitative and quantitative method. Three types of code switching proposed by Poplack (1980) and three main factor of code switching proposed by Holmes (2013). In order to analyze the factors of code switching, open-ended and close-ended questionnaire was given to the 18 English students in C class. There were 25 data which divided into tag switching, inter-sentential switching and intra-sentential switching. The type of code switching which mostly used by the English students is intra-sentential switching. According to the questionnaire, social factor such as participant, status, and solidarity have an important roles in influencing the code switching.